Effects of interface layers on the performance of annular thermoelectric generators. (15th March 2018) - Zhang, A.B.; Wang, B.L.; Pang, D.D.; He, L.W.; Lou, J.; Wang, J.; Du, J.K.
Abstract: The impedances of interface layers play essential role in annular thermoelectric generators (ATEGs) with relatively short thermoelectric couple, especially in the ATEG microdevices. This paper provides a theoretical model to investigate the effect of external and/or internal interface layers on the performance of ATEGs. Solutions for optimum current and imposed electric resistance at the maximum output power and maximum conversion efficiency of the ATEG are derived. Some simplified solutions at maximum output power are presented, and they are proved to be good approximations by comparing numerical results with a realistic ATEG subjected to the different applied temperature loadings. It is found that the performance of ATEGs has a significant reduction when the influence of interface layers is taken into consideration, and ideal solutions are only useful for the realistic ATEGs with a relatively long thermoelectric couple. This paper will be helpful in designing of the realistic ATEG devices. Highlights: An analytical model for the realistic annular thermoelectric generators (ATEGs) is developed. Effects of interface layers on the performance of ATEGs are investigated. Optimized annular shaped parameters and simplified solutions are presented.